Household Food Insecurity and the Factors Influencing Growth and Nutrition Among Under-5 Children in Hubballi, India: A Case-Control Study - Joshi, Anjana R; Shaikh, Rizwana B; Andanigoudar, Kashavva B; Teli, Rohit D; Tilagul, Saiprasad (National Journal of Community Medicine, 2025)
Background: Household Food Insecurity is one of the key determinants of chronic undernutrition in Indian children. Other factors include maternal factors, feeding practices, socio- sociocultural and environmental factors. The study was conducted to compare household food insecurity and other factors among undernourished and normal children aged < 5 years. Methodology: A community-based case-control study was conducted among PEM cases and normal controls in Hubballi using a pretested, semi-structured, validated questionnaire. Food insecurity was assessed using the standard USFAID household food insecurity scale. Height-for-age, weight-for-age, and weight-for-height Z scores were calculated using WHO Anthro PC. Results: Food Insecurity was found in 42% of the cases and 30% of the controls with 10% of the cases having severe food insecurity. There was a significant difference in the mean scores of household food insecurity among cases and controls. Food insecurity, low birth weight, illness, weaning initiation < 6 months of age, children without deworming, and the children who did not attend the under-5 clinic had higher odds of being malnourished. Conclusion: Household food insecurity is one of the important preventable risk factors for malnutrition. Creating awareness and proper utilization of health services has a positive impact on the child’s growth and development.